What is the solution of the pair of linear equations 37x + 43y = 123, 43x + 37y = 117?
(a) x = 2, y = 1 (b) x = −1, y = 2
(c) x = −2, y = 1 (d) x = 1, y = 2
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
CBSE Class 10 Sample Paper for 2022 Boards - Maths Basic [MCQ]
Question 2 Important
Question 3
Question 4 Important
Question 5
Question 6
Question 7 Important
Question 8
Question 9 Important
Question 10
Question 11 Important
Question 12
Question 13
Question 14 Important
Question 15
Question 16 Important
Question 17
Question 18
Question 19 Important
Question 20 Important
Question 21
Question 22
Question 23 Important
Question 24
Question 25 Important
Question 26 Important
Question 27
Question 28
Question 29 Important
Question 30 Important
Question 31
Question 32 Important
Question 33 Important
Question 34
Question 35
Question 36 Important
Question 37 Important
Question 38
Question 39 Important
Question 40 You are here
Question 41 (Case Based Question) Important
Question 42 (Case Based Question)
Question 43 (Case Based Question) Important
Question 44 (Case Based Question) Important
Question 45 (Case Based Question)
Question 46 (Case Based Question) Important
Question 47 (Case Based Question) Important
Question 48 (Case Based Question)
Question 49 (Case Based Question)
Question 50 (Case Based Question) Important
CBSE Class 10 Sample Paper for 2022 Boards - Maths Basic [MCQ]
Last updated at May 29, 2023 by Teachoo
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
Question 40 What is the solution of the pair of linear equations 37x + 43y = 123, 43x + 37y = 117? (a) x = 2, y = 1 (b) x = −1, y = 2 (c) x = −2, y = 1 (d) x = 1, y = 2 Given equations 37𝑥 + 43𝑦 = 123 …(1) 43𝑥 + 37𝑦 = 117 …(2) Adding both equations (1) and (2) (37𝒙 + 43𝒚) + (43𝒙 + 37𝒚) = 123 + 117 (37𝑥 + 43𝑥) + (43𝑦 + 37𝑦) = 240 80𝑥 + 80𝑦 = 240 80(𝒙 + 𝒚) = 240 𝑥 + 𝑦 = 240/80 𝑥 + 𝑦 = 3 Now, subtracting (1) and (2) (37𝒙 + 43𝒚) − (43𝒙 + 37𝒚) = 123 − 117 (37𝑥 − 43𝑥) + (43𝑦 − 37𝑦) = 8 −8𝑥 + 8𝑦 = 8 8(−𝒙 + 𝒚) = 8 −𝑥 + 𝑦 = 8/8 −𝑥 + 𝑦 = 1 Adding (3) and (4) (𝑥 + 𝑦) + (−𝑥 + 𝑦) = 3 + 1 2y = 4 y = 4/2 y = 2 Putting y = 2 in (3) 𝑥 + 𝑦 = 3 𝑥 + 2 = 3 𝑥 = 3 − 2 𝑥 = 1 ∴ x = 1, y = 2 So, the correct answer is (d)